Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Nilai Perusahaan Properti dan Real Estate - Vianti, Madu; Zakaria, Adam; Fauzi, Achmad (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to analyze and test the influence of profitability, leverage, and firm’s size on the value of property and real estate companies listed on the Indonesia Stock Exchange for the period 2019-2022. Providing information about profitability, leverage, and firm’s size is one way to avoid conflicts between management and company owners that could affect the firm’s value. The method used in this study includes descriptive analysis, classical assumption tests, multiple linear regression analysis, t-test statistics, coefficient of determination, and model feasibility tests. The sampling technique employed in this study is purposive sampling, with 76 data samples. The results of this study indicate that, partially, profitability does not have a significant effect on the firm’s value. Leverage has a negative effect on the firm’s value, while firm’s size has a positive effect on the value of property and real estate companies. The coefficient of determination indicates that profitability, leverage, and firm’s size collectively influence the value of property and real estate companies listed on the Indonesia Stock Exchange for the period 2019-2022 with an impact of 12.4%.